Transformation of the Activities of National Cultural Centers (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The article examines the transformation of the activities of national cultural centers in the context of global digitalization. The key areas of digital activity are analyzed: the creation of virtual exhibitions, online festivals, educational platforms and interaction formats. Special attention is paid to the problems of cultural homogenization, digital inequality and the preservation of authenticity in the digital environment. Examples of successful international initiatives implemented by the British Council, the Goethe Institute, Rossotrudnichestvo and UNESCO are given. Based on the collected data, three strategically important areas have been identified for improving the effectiveness of cultural diplomacy: ensuring equal access to digital resources, taking into account the local context, and overcoming language barriers.